A phenomenological study of the experience of tribal stigma among documented male Venezuelan migrants in Trinidad. (4th May 2021) - Peters, Kevin; Berkeley, Bennie
ABSTRACT: The current study explored the lived experiences of tribal criminal stigma among 15 documented male Venezuelan migrants residing along the East-West corridor of Trinidad and Tobago. Data were collected using a convenience sample. This is because participants were members of a volleyball club who were accessible after practice on Sunday mornings and Tuesday nights. A focus group discussion was conducted with 11 participants and semi-structured interviews held with four (4) individuals who were absent from the focus group session. This study explored one (1) central and three (3) secondary research questions. The data were analysed using Maxqda 2020. The analysis produced four (4) major themes: (1) vicarious stigma(2) antagonistic or pro-criminal conditions (financial strain, deskilling and proletarianisation, culture shock, labelling, victimisation, institutional backwardness and language barriers), (3) integration or preventive opportunities (blockages to criminal conduct such as social capital, social bonds, social control and social adaptation, and (4) bifurcated vision:'hopeful returnable' and 'assimilationist.'Major findings of the secondary research questions were compared and defined as 'theblocked pathway hypothesis'.